Appraisement of genetic variability and character association of kenaf (Hibiscus cannabinus): Genetic variability and character association of kenaf - Ahmed, Jubayer; Mahmud, Firoz; Sultana, Sharmin; Shamsuzzaman, Md (SAARC Journal of Agriculture, 2022)
Twenty five genotypes of Kenaf (Hibiscus cannabinus L.) from different geographic origins were grown at the Central Jute Agricultural Experiment station of Bangladesh Jute Research Institute (BJRI), Jagir, Manikganj to study their variability, correlation for nine morphological characters. Significant variation was found for all the characters among the genotypes. PCV was greater than GCV and high GCV values were observed for green weight with leaves, green weight without leaves, stick weight and fibre weight. The high heritability (more than 85%) coupled with high genetic advance in percent of mean were observed for most of the traits. All the characters except green bark thickness and internode length showed significant and positive correlation with fibre weight. Path co-efficient analysis revealed that green weight with leaves, green weight without leaves, green bark thickness and stick weight showed positive direct effect on fibre yield. Considering these agronomic performance genotypes G22 and G25 are suggested for future hybridization program. SAARC J. Agric., 20(2): 31-42 (2022)